PV/WT Integrated System Using the Gray Wolf Optimization Technique for Power Quality Improvement - Goud, B. Srikanth; Rami Reddy, Ch.; Naga Sai kalyan, Ch.; Udumula, Ramanjaneya Reddy; Bajaj, Mohit; Abdul Samad, Bdereddin; Shouran, Mokhtar; Kamel, Salah (Frontiers in Energy Research, 2022)
This paper presents the integration of renewable energy sources such as photovoltaics, wind, and batteries to the grid. The hybrid shunt active power filter (HSHAPF) is optimized with the Gray wolf optimization (GWO) and fractional order proportional integral controller (FOPI) for harmonic reduction under nonlinear and unbalanced load conditions. With the use of GWO, the parameters of FOPI are tuned, which effectively minimizes the harmonics. The proposed model has effectively compensated the total harmonic distortions when compared with without the filter and with the passive filter, the active power filter with a PI controller, and the GWO-FOPI-based controller. The performance of the proposed controller is tested under nonlinear and unbalanced conditions. The parameters of the FOPI controller are better tuned with the GWO technique. The comparative results reflect the best results of GWO-FOPI-based HSHAPF. The suggested controller is built in the MATLAB/Simulink Platform.